2013
DOI: 10.1007/s11255-013-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic data of adult native biopsy-proven renal diseases in Croatia

Abstract: PURPOSE: There is a paucity of epidemiological data on biopsy-proven renal disease in Croatia. The purpose of this report is a review of clinical and histological data, over a period of 15 years, from the single biggest adult native renal biopsy centre in Croatia.METHODS: This report includes data from 922 adult native renal biopsies in patients referred from the whole country and performed in our centre from 1996 till February 2012. Data on age, gender, serum creatinine, urine sediment, 24-hour proteinuria, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…24 Several post studies revealed that long duration of diabetes, the presence of diabetic retinopathy and poor glycaemic control may correlate with DN. 5,10,12,[24][25][26] Combination with the results of this study, diabetic retinopathy and glycaemic control are significant predictors for the identification of NDRD and DN.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…24 Several post studies revealed that long duration of diabetes, the presence of diabetic retinopathy and poor glycaemic control may correlate with DN. 5,10,12,[24][25][26] Combination with the results of this study, diabetic retinopathy and glycaemic control are significant predictors for the identification of NDRD and DN.…”
Section: Discussionsupporting
confidence: 67%
“…Identifying and monitoring DN relies upon assessments of kidney function, usually with an eGFR <60 mL/min/1.73 m 2 , and kidney damage, usually by estimation of albuminuria >30 mg/g creatinine . Several post studies revealed that long duration of diabetes, the presence of diabetic retinopathy and poor glycaemic control may correlate with DN . Combination with the results of this study, diabetic retinopathy and glycaemic control are significant predictors for the identification of NDRD and DN.…”
Section: Discussionsupporting
confidence: 64%
“…Of note, MN was more commonly identified than FSGS for adults presenting with the nephrotic syndrome. This is also seen in Korea, Japan, China, Italy and Spain, whereas FSGS is more prominently seen in most recent studies from Malaysia, USA, Croatia and Brazil …”
Section: Discussionmentioning
confidence: 63%
“…The average patient age at biopsy was 48 ± 17 years, which is at the higher end of adult populations worldwide – 39 (±15) years in Romania and Serbia; 47–50 (±18) years in USA, Northern Ireland and Croatia; and 52 (±14) years in France . This study suggests that GN incidence increases with age, mainly attributable to the increasing incidence of CrGN, DN and MN with age.…”
Section: Discussionmentioning
confidence: 67%
“…The most frequent histological patterns related to primary NS in adults are MN, FSGS and MCD [52,53] . However, cases of NS were also found to be due to diabetes, systemic lupus erythematosus (SLE), infections, multiple myeloma, amyloidosis or neoplasias [54] .…”
Section: Nephrotic Syndromementioning
confidence: 99%